Macronutrient signature of dietary generalism in an ecologically diverse primate in the wild. (30th April 2018) - Cui, Zhen-Wei; Wang, Zhen-Long; Shao, Qi; Raubenheimer, David; Lu, Ji-Qi
Abstract : Theory predicts that animals with a broad diet should be capable of using macronutrients (protein, fats, and carbohydrates) flexibly, such that a shortfall in one can be made up by additional intake of another. We used Rhesus macaques, a highly generalist primate, to test this in the wild. Our results strongly support the theory, and raise the question of why the same does not apply to the most generalist primate of all, humans. Abstract: A question of considerable importance is why some animals are able to succeed on a wide range of diets whereas others are more tightly constrained. Theory predicts that generalists should show a flexible response for macronutrient regulation in the face of ecologically driven constraint on the nutritional balance of available foods, which in the modeling framework of nutritional geometry has been quantitatively characterized as an "equal distance" regulatory model. This prediction, which has empirical support from several laboratory studies on insects, has not been tested for any generalist animal in the wild, nor for any vertebrate. We performed the first such test, using dawn-to-dusk focal animal observations over 3 years (2013–2015) of rhesus macaque monkeys ( Macaca mulatta tcheliensis ), a species that among primates is second only to humans in ecological generalism. Results showed, as predicted, that macronutrient regulation conformed closely to the equal distance pattern and differed markedly from the other, ecologically more-specialized primate species that have been studied to date. The same was independently true for lactating and non-lactating macaques, but lactating females had substantially higher intake of macronutrients, as well as the non-nutritional food components, indigestible fiber and tannins. This demonstrates that equal distance regulation by non-lactating monkeys was not an artefact of confounding constraints such as restricted food availability or an upper limit to the ingestion of dietary fiber or plant tannins, but a strategic regulatory response to variation in dietary macronutrient balance. We discuss implications of our results for the most generalist primate of all, humans.